2021
DOI: 10.1021/acssuschemeng.1c02696
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Promising Covalent-Organic Frameworks for Decarburization and Desulfurization from Biogas via Computational Screening

Abstract: Efficient removal of hydrogen sulfide and carbon dioxide is essential for biogas purification, which is still a longstanding challenge economically and environmentally. Recently, covalent-organic frameworks (COFs) have become competitive candidates for acid gases capture. In this study, high-throughput computational screening of a database containing 382 computation-ready experimental COFs were employed to establish structure-performance relationships and to identify the topperforming materials for H 2 S and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Lennard–Jones (LJ) interactions and Ewald electrostatic interactions were used to calculate gas–gas interactions and gas–COF framework interactions. [ 24 ] Considering CO 2 and N 2 as rigid linear molecules, three charged LJ interaction sites were chosen for CO 2 and N 2 . The LJ potential parameters for CO 2 and N 2 were from the TraPPE model reported by Potoff and Siepmann.…”
Section: Methodsmentioning
confidence: 99%
“…Lennard–Jones (LJ) interactions and Ewald electrostatic interactions were used to calculate gas–gas interactions and gas–COF framework interactions. [ 24 ] Considering CO 2 and N 2 as rigid linear molecules, three charged LJ interaction sites were chosen for CO 2 and N 2 . The LJ potential parameters for CO 2 and N 2 were from the TraPPE model reported by Potoff and Siepmann.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al reported computational screening of COFs for simultaneous desulphurization and decarbonization for biogas production. 277 The results indicated that a limiting cavity diameter (LCD) of 12.5 Å and porosity of 0.65 was quite suitable for simultaneous operation. Aksu et al computationally screened COF materials for removing H 2 S and CO 2 from natural gas mixtures and highlighted the superior performance of several COFs to existing MOFs and zeolites.…”
Section: Processes For Carbon Capture Using Cofs: Developments and Ch...mentioning
confidence: 99%
“…38 COF-gas and gas−gas interactions were performed using the Lennard-Jones (LJ) potential description. The Dreiding force field is used to describe the elemental composition of COFs, 39 and the Universal Force Field (UFF) is used to describe other metallic elements, 40 and the work of Wang et al 41 have demonstrated that the "UFF_Dreiding" hybrid force field is in good agreement with experiment. Due to the presence of polar gas molecules, charge equilibrium (Qeq) calculations are used to quickly compute the partial charges of the atomic framework of COFs.…”
Section: Molecular Simulation and Calculation Of Membranementioning
confidence: 99%